Respiratory health service utilization of children with neuromuscular disease. Issue 10 (21st August 2018) - Rose, Louise; McKim, Douglas; Leasa, David; Nonoyama, Mika; Tandon, Anu; Bai, Yu Qing; Goldstein, Roger; Amin, Reshma; Katz, Sherri; Gershon, Andrea
Abstract: Objectives: To quantify health service utilization including assessment, monitoring, and treatment of respiratory complications of children with neuromuscular disease (NMD), identifying practice variation and adherence to guideline recommendations at a population level. Methods: North American population‐based cohort study (2003‐2015) of children with NMD using hospital diagnostic and physician billing codes within health administrative databases. Results: We identified 18 163 children with NMD. Mean (SD) age was 7.8 (5.6) years with 40% ≤5; 45% were female. Most common diagnoses were cerebral palsy (50%) and spina bifida (16%); 8% had muscular dystrophy. From fiscal years 2003‐2014, 15 600 (86%) children went to an emergency department on average 3.5 times every 3 years; 6575 (36%) for respiratory reasons. 8788 (48%) were admitted to hospital with 2190 (12%) for respiratory reasons and 2451 (13%) required intensive care. Respiratory specialist outpatient visits occurred for 2226 (12%) children on average 6.5 visits every 3 years; 723 (4%) had in‐hospital respiratory specialist consultation. Pulmonary function testing was conducted in 3194 (18%) children on average 2.4 times every 3 years; sleep studies in 1389 (8%). Conclusion: In this population‐based study of children with NMD, healthcare utilization for respiratory complications was considerable. Frequency of respiratory specialist consultation, monitoring of respiratory function and sleep disordered breathing was variable but on average reflected professional society recommendations. Children with NMD are frequent ED users suggesting a need to improve community and social supports. We did not detect reduced access to respiratory monitoring or specialist consultation in adolescents transitioning to adult services.